Increasing forest benefits through the leasehold forestry and livestock programme: improving its implementation and effectiv eness - Albano, A.; Regmi, B; Kumar, C.; Belcher, B. (Center for International Forestry Research, 2008)
Nepal introduced various community based forest management (CBFM) programmesthat aim to improve forest management while improving the livelihoods of the forest dependent poor. One of these programmes is the Leasehold Forestry and Livestock Programme (LFLP). Various studies have demonstrated its positive impacts but severa studies also pointed out its unintentional negative impacts. This policy brief presents implementation and related design constraints facing the LFLP and suggests ways to resolve them and improve programme outcomes. This brief is based on our review study of the institutional constraints to the LFLP in achieving its poverty alleviation objective. Proper implementation of the programme is constrained by a lack of awareness of the people about it, which can be attributed to the lack of capacity in the implementing line agencies, and also to programme design weaknesses. To improve its effectiveness and impact, awareness campaigns should be improved using diverse modes of communication, more line agencies should be involved in the implementation by transferring the implementation responsibility to a district-level project coordination committee, and some programme provisions should be changed in favour of the poor.